Analisis Strategi Peningkatan Ekspor Rumput Laut Indonesia di Pasar Global - Sofiyanti, Jia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Indonesia, a major producer of marine resources, has a significant potential in the global ocean. However, its contribution to the global ocean is still low compared to its potential. Therefore, analyzing Indonesia's ocean resource management strategy is crucial to boost local economic growth and improve the livelihoods of the local population.One challenge in managing the Indonesian ocean resources is the lack of technology in marine management and research. Many fishermen use traditional methods that are inefficient and negatively impact product quality. Despite this, the volume of marine resources can be a significant contributor to the local economy.The study aims to develop a systematic literature review (SLR) to analyze Indonesia's ocean resource management strategy in the global ocean. SLR is a systematic and structured method for identifying, evaluating, and integrating relevant research findings from various sources. The data collected from various journals, articles, and reports on the Indonesian ocean resources industry can be analyzed using qualitative methods to identify patterns and themes, and to develop effective strategies for increasing the Indonesian ocean resource management.